Prevalence and Economic Importance of Stilesia Hepatica in Small Ruminants Slaughtered at Helmix Abattoir, Bishoftu, Ethiopia (Global Journal of Medical Research, 2015)
Across sectional study was conducted at HELMEX abattoir, Debrezeit town, central highlands of Ethiopia from October 2010 to march 2011 on 800 young and adult sheep and goats (400 sheep and 400 goats) originated from different areas of Ethiopia. The objectives of the study were to determine the prevalence of Stilesia hepatica in young and adult sheep and goats brought to the slaughter house from different parts of Ethiopia and to assess the direct financial loss incurred due to rejection of Stilesia hepatica infected livers. Pearson's chi-Square (x2) test was calculated to determine the degree of association of S.hepatica infection with species (sheep and goats), origin and age (young and adult) of the animals. P-value less than 0.05 were considered to be statistically significant.
Keywords: goats; sheep prevalence; stilesia hepatica